Characterisation of mortarless refractory masonry joints under elevated temperatures - Gajjar, Pratik Naresh (2023)
Refractory linings are commonly employed in Industrial vessels used in high-temperature processes to protect them against extreme working environments. The working lining of an industrial steel ladle frequently employs mortarless refractory masonry to contain the molten steel and limit heat losses. Such masonry lining undergoes high thermomechanical loads, primarily due to thermal expansion arising from thermal and mechanical boundary conditions. Dry joints, described as a physical break in the continuum, reduce some of these effects. Therefore, understanding dry joints is an essential factor for developing numerical constitutive models that employ a meso or macro modelling approach. This work aims to experimentally investigate the normal compressive behaviour of dry joints in refractory masonry. For this purpose, various refractory specimens of alumina-spinel material are tested from ambient temperature to 1200 °C. The results obtained from these experiments are then used to identify critical joint parameters with different mathematical models for the interface. The outcome describes exponential joint closing behaviour with respect to the force applied. It was observed that the pressure required to close a joint reduces with an increase in temperature. The exponential model was then used to numerically simulate the joint closure of mortarless refractory masonry. Finally, numerical and experimental results were compared.